Peningkatan Kinerja Guru SMK Melalui Penguatan Literasi Digital Dan Kepemimpinan Melayani - R. Nur Amalia; Sri Sundari; Marisi Pakpahan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
Teacher performance indicators can be the basis for planning teacher performance assessment, which includes teacher planning in learning activity programs, learning procedures, and learning assessment. Digital literacy is very important in the current digital era, because it allows individuals, especially teachers, to adapt and communicate effectively in various situations. aspects of life and career. Apart from that, teachers can also apply a servant leadership style, namely a leadership model that places service as the main priority. This research aims to determine efforts to improve teacher performance by strengthening variables related to teacher performance, namely Digital Literacy and Service Leadership. The research results concluded: 1) there is a positive and significant relationship between Digital Literacy and Performance; 2) there is a positive and significant relationship between Servant Leadership and Performance; 3) there is a positive and significant relationship between Digital Literacy and Servant Leadership together with Teacher Performance. This shows that strengthening digital literacy and servant leadership can improve teacher performance.